2016
DOI: 10.1088/0953-8984/28/47/475801
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thickness-dependent optical energy gap of ALD-grown ultra-thin CuO films

Abstract: Usually an inverse square relation between the optical energy gap and the size of crystallites is observed for semiconducting materials due to the strong quantum localization effect. Coulomb attraction that may lead to a proportional dependence is often ignored or considered less important to the optical energy gap when the crystallite size or the thickness of a thin film changes. Here we report a proportional dependence between the optical energy gap and the thickness of ALD-grown CuO thin films due to a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
(121 reference statements)
2
8
0
Order By: Relevance
“…Recently, Wang et al predicted that the indirect band gap of Cu 4 O 3 is 1.59 eV [4]. As for CuO, the type of band gap of CuO remains controversial; in some studies its band gap is suggested to be direct [16,17,18], but it is considered that its band gap is indirect in other studies [1,19,20], and its accurate band gap value is still a greater challenge for electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al predicted that the indirect band gap of Cu 4 O 3 is 1.59 eV [4]. As for CuO, the type of band gap of CuO remains controversial; in some studies its band gap is suggested to be direct [16,17,18], but it is considered that its band gap is indirect in other studies [1,19,20], and its accurate band gap value is still a greater challenge for electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the absorption coefficient α of CuO-0.5Ni is plotted in Figure a based on the formula α = 4 πk /λ, where λ is the wavelength of the incident light. As can be seen, the maximum α value is ∼1.2 × 10 6 cm –1 , which is obviously larger (∼10 times) than that obtained from other experimental data. That means a stronger ability to capture photons can be obtained, which is favorable for greater photocurrent in optoelectronic devices. The optical conductivity σ r at the photon energy of 3.3, 3.75, and 4 eV is plotted in Figure b.…”
Section: Resultsmentioning
confidence: 78%
“…Recently, we demonstrated the possibility to tune the optical bandgap of different semiconducting metal oxide thin films through precise film thickness control (CuO), [22] or insertion of monomolecular organic layers within the metal oxide matrix (TiO 2 , ϵ‐Fe 2 O 3 ) [23,24] . These thin films were grown through ALD (atomic layer deposition) and MLD (molecular layer deposition) cycles, for the inorganic and organic layers, respectively.…”
Section: Figurementioning
confidence: 99%